Juridical Analysis of the Duality of Cryptocurrency Status as a Payment Instrument and Investment Commodity in Indonesian Regulation - Gilvina Grace B.A.; Muhammad Nurcholis Alhadi; Surahman Surahman; Elviandri Elviandri (Badan Penerbit STIEPARI Press, 2025)
Cryptocurrency has emerged as a global innovation since the launch of Bitcoin in 2009, underpinned by blockchain technology that offers enhanced efficiency and transparency. Despite its potential, cryptocurrency presents complex legal challenges, particularly concerning its regulatory status. In Indonesia, cryptocurrency faces a dual regulatory framework: it is prohibited as a means of payment by Bank Indonesia pursuant to Law No. 7 of 2011 on Currency, yet simultaneously recognized as a tradable investment commodity by the Commodity Futures Trading Regulatory Agency (Bappebti). This study aims to analyze the implications of this duality for Indonesia’s national regulatory system. Using normative legal research and a statutory approach, the study reveals significant legal uncertainty arising from institutional regulatory inconsistencies. Such uncertainty may impede innovation and compromise consumer protection. Therefore, regulatory harmonization is essential to ensure legal certainty and adaptability, drawing on the theories of legal certainty and progressive law.